Procedure for demand forecasting in a cuban micro and SME - Fernández Cabrera, Jimmy Ernesto; Llanes , Aramis Alfonso; Ramos Gómez , Rafael A. (EASI: Engineering and Applied Sciences in Industry, 2022)
Demand forecasting is a fundamental element in the planning of micro, small and medium-sized enterprises (MSMEs). In this sense, the objective of this work is to develop the monthly demand forecast of the production in a footwear manufacturing company, using the methodological tool that best suits the conditions of the entity under study. The proposed procedure allows the selection of the forecast model that best suits the specificities of the demand, as well as develops a group of equations that facilitate the development of the forecast considering the predominant trend and seasonality patterns in the historical data series. The practical application of the proposal highlights the advantage of adopting techniques, methods and tools of Operations Management in Mypymes. With this application, in a footwear manufacturing company, it is possible to identify the most appropriate forecasting method according to the characteristic parameters of the studied demand (trend and seasonality), as well as to forecast the monthly sales of shoes for the year 2022 with an accurate estimated level of precision (according to the error measure considered).
Keywords: operations management; SMEs; demand forecasting